Impact of different sofosbuvir based treatment regimens on the biochemical profile of chronic hepatitis C genotype 4 patients. (3rd August 2017) - Elsharkawy, Aisha; Eletreby, Rasha; Fouad, Rabab; Soliman, Zeinab; Abdallah, Mohamed; Negm, Mohamed; Mohey, Mohammad; Esmat, Gamal
ABSTRACT: Background : Huge efforts have been made to control chronic HCV in Egypt with introduction of Direct-Acting Antivirals (DAAs). Current study aims at evaluating effect of various DAA regimens on liver biochemical profile and haematological indices during treatment. Methods : 272 patients with chronic HCV genotype 4 treated by different DAA regimens (SOF/RBV, SOF/DAC ± RBV, SOF/SIM) for a duration of 12 or 24 weeks in Kasr Alainy Viral Hepatitis Center, Cairo University were followed up for serum bilirubin (BIL), albumin (ALB), alanine transaminase (ALT), aspartate aminotransferase (AST), prothrombin concentration, international normalized ratio (INR), and CBC at baseline, week-4 and end of treatment. Results : Mean age was 54 years. Males comprised 64.7%, 72.4% were treatment-naïve, 39% were cirrhotic. Overall SVR12 rate was (93.4%). With all regimens, ALT and AST declined after treatment. In cirrhotics, there was a rise in BIL and INR; with no change in ALB and a decrease in White blood cells. Drop in Hemoglobin and platelets in cirrhotic patients were noted with SOF/RBV, while SOF/SIM showed rise in BIL. Conclusion : DAAs are safe and effective in genotype 4 chronic HCV patients. It improves liver necro-inflammatory markers in cirrhotics and non-cirrhotics. Cirrhotic patients require careful observation being more vulnerable for treatment related complications.